Autologous T cell responses to primary human colorectal cancer spheroids are enhanced by ectonucleotidase inhibition. Issue 4 (8th July 2022) - Bonnereau, Julie; Courau, Tristan; Asesio, Nicolas; Salfati, Delphine; Bouhidel, Fatiha; Corte, Hélène; Hamoudi, Sarah; Hammoudi, Nassim; Lavolé, Julie; Vivier-Chicoteau, Justine; Chardiny, Victor; Maggiori, Leon; et al.
Abstract : Objective: T cells are major effectors of the antitumoural immune response. Their activation by tumour-associated antigens can unleash their proliferation and cytotoxic functions, leading to tumour cell elimination. However, tumour-related immunosuppressive mechanisms including the overexpression of immune checkpoints like programmed cell death protein-1 (PD-1), are also engaged, promoting immune escape. Current immunotherapies targeting these pathways have demonstrated weak efficacy in colorectal cancer (CRC). It is thus crucial to find new targets for immunotherapy in this cancer type. Design: In a prospective cohort of patients with CRC, we investigated the phenotype of tumour-related and non-tumour related intestinal T cells (n=44), particularly the adenosinergic pathway, correlating with clinical phenotype. An autologous coculture model was developed between patient-derived primary tumour spheroids and their autologous tumour-associated lymphocytes. We used this relevant model to assess the effects of CD39 blockade on the antitumour T cell response. Results: We show the increased expression of CD39, and its co-expression with PD-1, on tumour infiltrating T cells compared with mucosal lymphocytes. CD39 expression was higher in the right colon and early-stage tumours, thus defining a subset of patients potentially responsive to CD39 blockade. Finally, we demonstrate in autologous conditions that CD39 blockade triggers T cell infiltration and tumour spheroid destruction in cocultures. Conclusion: In CRC, CD39 is strongly expressed on tumour infiltrating lymphocytes and its inhibition represents a promising therapeutic strategy for treating patients.